Comparison of Effects of Single Visit Full Mouth Ultrasonic Debridement with Two Visits Partial Mouth Ultrasonic Debridement in the Treatment of Chronic Periodontitis (Medical Forum Monthly, 2024)
Objective: The objective of this study is to compare the clinical effects of single visit full mouth ultrasonic debridement to those of two visit partial mouth ultrasonic debridement up to one month following periodontal treatment.Study Design: An Experimental & Interventional studyPlace and Duration of Study: This study was conducted at the Out-patient Department (Periodontology) of Isra Dental College Hospital, Isra University, Hyderabad from April 2017 to September 2017.Materials and Methods: Sixty patients of moderate chronic periodontitis were selected through purposive non-probability sampling. All patients were examined at baseline i.e. before treatment, followed up by 1 week, and 1 month respectively. Probing pocket depth (PPD), clinical attachment level (CAL) Index and Plaque index (PI) was measured.Results: After treatment, both groups showed signiﬁcant improvement in clinical parameters. Full-mouth treatments resulted in greater improvements in full-mouth mean plaque percentage, probing pocket depth and bleeding on probing as conventional therapy. When data was analyzed based on pocket depth and tooth type, there was no difference between groups in attachment gains. The full-mouth groups demonstrated greater reduction in BOP% and number of pockets and the total treatment time was signiﬁcantly shorter.Conclusion: This study concluded that Full mouth has more beneficial effects on reducing gingival inflammation, plaque level, probing depth, but not significant improvement in clinical attachment level as compare to partial mouth. Moreover, full-mouth ultrasonic debridement provides clinically relevant improvements in the periodontal treatment.